Stereotypes of physical appearance and labor market chances - Mahmood Arai; Marie Gartell; Magnus Rödin; Gülay Özcan (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2016)
Using an experimental setup involving 436 case workers at the Swedish Public Employment Service (SPES) as subjects and the profile photographs and recorded voices of 75 jobseekers as treatments, we report results indicating that male case workers tend to favor jobseekers perceived as having a stereotypical Swedish appearance when they select candidates to be recommended for labor market programs (LMP). This bias represents a roughly 50-percent greater chance of being selected if you compare the candidate with the highest score with regard to stereotypical Swedish looks (8/10) with the candidate with the lowest score (3/10) in our sample.
Keywords: J7; J15; 330; Discrimination; Ethnic Discrimination; Racial Discrimination; Stereotypes; Noncognitive Attributes